SISTEM POINT OF SALES (POS) DENGAN PENERAPAN MODEL WATERFALL PADA TOKO NINGNONG CIPUTAT (Studi Kasus : TOKO NINGNONG CIPUTAT TANGERANG SELATAN) - Maulana Nurul Hidayat; Susanna Dwi Yulianti Kusuma (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Sales is an integrated effort to develop a strategic plan that is directed at satisfying the needs and desires of buyers to get sales that generate profits (Marwan A, 1986). Sale is a transfer of rights to objects. From this explanation, working in transferring or transferring goods and services requires people who are in the field of sales such as trade operations, agents, service representatives, and marketing representatives. From the above understanding that the lifeblood of a merchant's business, especially the "Ningnong Ciputat" store, is sales. The "Ningnong Ciputat" shop is a trading unit that provides all human needs ranging from basic needs, basic necessities, etc. With many products needed, a ledger is needed that is used to record product names and prices, as well as a transaction ledger that is used to record all sales transactions that occur. With this method of recording, employees have to put a price tag on each product, besides that, making at the end of the month has difficulty because they have to recap all sales transactions recorded in the general ledger. This does not rule out the possibility of recording errors and the time used to make reports less effective and efficient.